New approaches for modelling vortex flow meters. Issue 2 (November 2020) - Dayev, Zhanat; Kairakbaev, Aiat; Duzheva, Alexandra; Sultanov, Nail
Abstract: The paper proposes a new model of a vortex flow meter, which is developed on the basis of modification of the basic equations of incompressible fluid hydrodynamics. The article deals with the modification of the Euler equation and the continuity equation of the flow. In this paper, dependencies are obtained for estimating the final standard uncertainty of flow rate using a vortex transducer. A detailed analysis of the influence of incompressible fluid flow parameters and the geometric dimensions of the vortex transducer on the final uncertainty of flow rate is performed. Recommendations are given for improving the method of flow rate using vortex transducers.